The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jdv.16000
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and management of sensitive skin: position paper from the special interest group on sensitive skin of the International Forum for the Study of Itch (IFSI)

Abstract: The special interest group on sensitive skin of the International Forum for the Study of Itch previously defined sensitive skin as a syndrome defined by the occurrence of unpleasant sensations (stinging, burning, pain, pruritus and tingling sensations) in response to stimuli that normally should not provoke such sensations. This additional paper focuses on the pathophysiology and the management of sensitive skin. Sensitive skin is not an immunological disorder but is related to alterations of the skin nervous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 75 publications
0
63
0
Order By: Relevance
“…Patients who report a presumed allergy to cosmetics may in fact suffer from “sensitive skin.” This is a separate entity defined as “the occurrence of unpleasant sensations (stinging, burning, pain, pruritus and tingling sensations) in response to stimuli that normally should not provoke such sensations.” 2 It is not immunologically driven and should not be confused with allergic contact dermatitis (ACD).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who report a presumed allergy to cosmetics may in fact suffer from “sensitive skin.” This is a separate entity defined as “the occurrence of unpleasant sensations (stinging, burning, pain, pruritus and tingling sensations) in response to stimuli that normally should not provoke such sensations.” 2 It is not immunologically driven and should not be confused with allergic contact dermatitis (ACD).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of the literature showed that the levels of epidermal pH, sebum production and skin hydration were inconsistent [53]. Consequently, dry skin and sensitive can be associated, but sensitive skin cannot be reduced to being a manifestation of dry skin, and its management does not consist of the only application of emollients [12]. Nonetheless, it does not mean that there is no role of keratinocytes in sensitive skin and there are complex interactions between neurons and keratinocytes in sensitive skin [54].…”
Section: Arguments For Neuro-keratinocytic Interactionsmentioning
confidence: 99%
“…The IFSI special interest group on sensitive skin published a position paper on the pathophysiology and management of sensitive skin [12]. A multifactorial origin was suggested after the discussion of many putative mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitive skin affects approximately half of the population and is more frequent in women than in men (2,3). The pathophysiological mechanisms have been debated, and several hypotheses exist (4). Sensitive skin can be considered a result of a decrease in the skin tolerance threshold, which thereby impairs barrier function and leads to abnormalities in the cutaneous nervous system, making the skin hyperreactive (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiological mechanisms have been debated, and several hypotheses exist (4). Sensitive skin can be considered a result of a decrease in the skin tolerance threshold, which thereby impairs barrier function and leads to abnormalities in the cutaneous nervous system, making the skin hyperreactive (4)(5)(6). Sensitive skin can therefore be the clinical expression of neurogenic inflammation and can be modulated by many factors (7).…”
Section: Introductionmentioning
confidence: 99%